Implementation of Repeated Reading Method to Improve Elementary School Students' Reading Comprehension - Arsianti, Asma Alifta; Irvan, Moh. Farizqo; Ramadhani, Naswa; Lutfiani, Isna Anisa; Pernatasari, Armelitha Eka; Razin, Zulhan Arif (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2025)
This study aimed to determine the effectiveness of the repeated reading method in improving reading comprehension among third-grade students at SD Negeri Gisikdrono 2. The research was motivated by students' low reading comprehension skills, largely due to the lack of parental support for reading activities at home. A qualitative approach was employed, with purposive sampling used to select participants, including a class teacher and students. Data were collected through observation, interviews, questionnaires, and documentation, and were analyzed using descriptive qualitative methods. The results showed that the repeated reading method had a positive impact on students' reading comprehension, especially for those who initially struggled. After practicing repeated reading and answering comprehension questions, students showed noticeable improvement in understanding text content. Additionally, teacher involvement and parental support at home played a significant role in the success of this method. These findings suggest that the repeated reading method is an effective strategy to enhance reading comprehension skills in primary school students.